Behaviour of CFST members under compression externally reinforced by CFRP composites - Sundarraja, M. C.; Prabhu, G. Ganesh (Journal of Civil Engineering and Management, 2013)
This research is aimed at investigating the structural improvements of concrete filled steel tubular (CFST) sections with normal strength concrete externally bonded with fibre reinforced polymer (FRP) composites. For this study, compact mild steel tubes were used with the main variable being FRP characteristics. Carbon fibre reinforced polymer (CFRP) fabrics was used as horizontal strips (lateral ties) with several other parameters such as the number of layers and spacing of strips. Among twenty one columns, eighteen were externally bonded by CFRP strips having a constant width of 50 mm with a spacing of 20 mm and 40 mm and the remaining three columns were unbounded. Experiments were undertaken until column failure to fully understand the influence of FRP characteristics on the compressive behaviour of square CFST sections including their failure modes, axial stress-strain behaviour, and enhancement in load carrying capapcity. It was found that the external bonding of CFRP strips provides external confinement pressure effectively and intended to delay the local buckling of steel tube and also to improve the load carrying capacity further.